MOTIF OEDIPAL DALAM NOVEL CERITA CINTA ENRICOKARYA AYU UTAMI, TINJAUAN PSIKOANALISIS Oedipal Motif in the Novel Cerita Cinta Enrico By Ayu Utami, Psychoanalysis Review) - Samsiarni, NFN (Balai Bahasa Sumatra Barat, 2016)
AbstractThis article discusses the Oedipal motive in the novel entiled Cerita Cinta Enrico, experiencedby it main character Enrico that caused no completion Oedipal period, so he experienced theOedipus complex. This study uses the theory of psychoanalysis by Freud, psychosexualdevelopment of children and personality theory. The results showed that the Oedipus complexEnrico suffered due to the distance in the relationship between he and his mother. Themother, in the sexual development of Enrico appears as someone who is in control, thuscausing Enrico can’t express the feeling of love towards his mother. His sister’s death, Sandaand runaway mother to the new religion as a cause of maternal perceived Enrico ignore itspresence. Results of the analysis carried out showed a different pattern in the case of OedipalEnrico as described by Freud’s theory, namely the inhibitor son gets mother’s love. In Freud,the person who prevents children from expressing teir love to mother is a father figure, whilein the novel is itself a mother figure.AbstrakArtikel ini membahas tentang motif Oedipal yang dialami oleh tokoh Enrico yang disebabkan karenatidak tuntasnya masa Oedipalnya sehingga dia mengalami kompleks Oedipus. Penelitian inimenggunakan teori Psikoanalisis Freud, yaitu tentang perkembangan psikoseksual anak dan teorikepribadian. Hasil penelitian menunjukkan bahwa Enrico mengalami kompleks Oedipus yangdisebabkan adanya jarak dalam hubungan dia dan ibunya. Ibu, dalam perkembangan seksual Enricomuncul sebagai sosok yang memegang kendali sehingga menyebabkan Enrico tidak bisamenyampaikan perasaan cinta terhadap ibunya. Kematian kakaknya, Sanda dan pelarian ibunyapada agama baru dirasakan Enrico sebagai penyebab ibu mengabaikan kehadirannya. Hasil analisisyang dilakukan menunjukkan adanya motif Oedipal yang berbeda dalam kasus Enrico dengan apayang diuraikan oleh teori Freud, yaitu mengenai penghambat anak mendapatkan cinta ibunya. DalamFreud yang menghalangi anak mengekspresikan cinta pada ibu adalah sosok ayah, sedangkan dalamnovel ini adalah sosok ibu itu sendiri.